2020
DOI: 10.1371/journal.pone.0234448
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses revealed the effect of Funneliformis mosseae on genes expression in Fusarium oxysporum

Abstract: Soybean root rot is a typical soil-borne disease that severely affects the yield of soybean. Funneliformis mosseae is one of the arbuscular mycorrhizal fungi(AMF) dominant strains in soybean continuous cropping soil. The aim of this study was to providing an experimental basis for the study of the molecular mechanism underlying the alleviation of the obstacles associated with the continuous cropping of soybean by AMF. In this study, F. mosseae was inoculated in soil planted with soybean infected with Fusarium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The inhibitory abilities of this species against Fusarium and a wide range of other fungal phytopathogens have been reported in several studies [20]. These beneficial effects are related to the ability of F. mosseae to promote plant development and growth while enhancing disease resistance (i.e., improving host plant barriers, disrupting pathogen structure, and shielding plant tissues) [21,22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The inhibitory abilities of this species against Fusarium and a wide range of other fungal phytopathogens have been reported in several studies [20]. These beneficial effects are related to the ability of F. mosseae to promote plant development and growth while enhancing disease resistance (i.e., improving host plant barriers, disrupting pathogen structure, and shielding plant tissues) [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have reported that this strain can improve plant resistance to biotic stress against a wide range of phytopathogens, including Fusarium [20]. These beneficial effects are related to F. mosseae's ability to promote plant development and growth while enhancing disease resistance (i.e., improving host plant barriers, disrupting pathogen structure, and shielding plant tissues) [21,22].…”
Section: Introductionmentioning
confidence: 99%